Airway inflammation in sickle cell disease—A translational perspective. Issue 4 (4th January 2018) - De, Aliva; Manwani, Deepa; Rastogi, Deepa
Abstract: Asthma and sickle cell disease (SCD) are common chronic conditions in children of African ancestry that are characterized by cough, wheeze, and obstructive patterns on pulmonary function. Pulmonary function testing in children with SCD has estimated a prevalence of obstructive lung disease ranging from 13% to 57%, and airway hyper‐responsiveness of up to 77%, independent of a diagnosis of asthma. Asthma co‐existing with SCD is associated with increased risk of acute chest syndrome (ACS), respiratory symptoms, pain episodes, and death. However, there are inherent differences in the pathophysiology of SCD and asthma. While classic allergic asthma in the general population is associated with a T‐helper 2 cell (Th‐2 cells) pattern of cell inflammation, increased IgE levels and often positive allergy testing, inflammation in SCD is associated with different inflammatory pathways, involving neutrophilic and monocytic pathways, which have been explored to a limited extent in mouse models and with a dearth of human studies. The current review summarizes the existent literature on sickle cell related airway inflammation and its cross roads with allergic asthma‐related inflammation, and discusses the importance of further elucidating and understanding these common and divergent inflammatory pathways in human studies to facilitate development of targeted therapy for children with SCD and pulmonary morbidity.